PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK SISWA SEKOLAH DASAR DI ERA DIGITAL - Ahmad Nubli Syamili; Zulfitria Zulfitria (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research discusses the use of interactive learning media for elementary school students in the digital era. The research problem focuses on understanding the role of interactive learning media for elementary school students, particularly those based on modern applications or websites. The goal is for both teachers and students to be able to utilize the interactive learning media available around them, which will eventually influence the process and the final outcomes of learning. This research uses a qualitative methodology in the form of a literature review. Data is obtained from various sources such as research journals, articles, and previous scientific works. The research results show that there are many interactive learning media available around us, such as educational videos, digital learning platforms, interactive simulations, and educational games. In their implementation, there are issues that need to be addressed to ensure that interactive learning media can achieve maximum eflectiveness.